Reverse Engineer 5 Degrees of Freedom Robot Arm using Programmable Logic Controller (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Many types of robot arms have been developed in the market. Whenever a robot arm broke down, it is a challenge to do reverse engineer and repair the robot arm. This project has successfully reused the existing 5 degrees of freedom robot arm structure and electronic components while replacing the controller with a new Programmable Logic Controller (PLC) and LLD model. The project uses the existing DC servo motor, encoder, sensors, power supply, and interface board. Since the structure and most electronic components are already available, they are important to be analyzed and understood before they can be reused. Hence the reverse engineering activities are needed. In addition, a low-cost PLC is used to save cost. Thus, it is not possible to move all axes at the same time. Instead, the robot arm can only move one axis at a time. Additionally, the robot arm has been improved to be able to be programmed manually or automatically and repeat previously predetermined position sequences. In total, 90 rungs, 96 built-in commands, and custom functions have been used. The refurbished system is very stable and reliable.